1995
DOI: 10.1074/jbc.270.20.12269
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human Lecithin Cholesterol Acyltransferase Leads to Hyperalphalipoproteinemia in Transgenic Mice

Abstract: Lecithin cholesterol acyltransferase (LCAT) is a key enzyme which catalyzes the esterification of free cholesterol present in plasma lipoproteins. In order to evaluate the role of LCAT in HDL metabolism, a 6.2-kilobase (kb) fragment consisting of 0.851 and 1.134 kb of the 5'- and 3'-flanking regions, as well as the entire human LCAT gene, was utilized to develop transgenic mice. Three different transgenic mouse lines overexpressing human LCAT at plasma levels 11-, 14-, and 109-fold higher than non-transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 41 publications
4
75
1
Order By: Relevance
“…24 By contrast, decreased LCAT and PAF-AH activities in distinct HDL subfractions in HALP appear to be related to their redistribution between plasma lipoproteins, consistent with earlier data. 25,26 Specific antioxidative activity, PON, PAF-AH, and LCAT activities, and oxidative resistance of HDL subfractions were highest in the densest HDL3c subfraction and tended to decrease with decrement in HDL density. HDL-associated enzymes therefore may not only protect LDL but also protect PON/PAF-AH/LCAT-transporting HDL particles themselves against oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…24 By contrast, decreased LCAT and PAF-AH activities in distinct HDL subfractions in HALP appear to be related to their redistribution between plasma lipoproteins, consistent with earlier data. 25,26 Specific antioxidative activity, PON, PAF-AH, and LCAT activities, and oxidative resistance of HDL subfractions were highest in the densest HDL3c subfraction and tended to decrease with decrement in HDL density. HDL-associated enzymes therefore may not only protect LDL but also protect PON/PAF-AH/LCAT-transporting HDL particles themselves against oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility are earlier studies that showed that (a) other apolipoproteins found in HDL (e.g., apoA-II) can serve as ligands for SR-BI (28); and (b) adenovirus-mediated overexpression of SR-BI in apoA-I KO mice results in the loss of virtually all of the apoA-I-deficient HDL cholesterol (K. Kozarsky and M. Donahee, personal communication). There was a reduction in the amount of HDL-like cholesterol in the SR-BI/apoA-I double -KO relative to SR-BI KO (Figure 1a, open circles) mice, with the greatest reduction seen in the smallest, normal-sized HDL particles (fractions [29][30][31][32][33][34][35][36][37][38]. Therefore, in the context of a SR-BI KO background, the loss of apoA-I resulted in significant changes in the structure of the HDL (e.g., no apoA-I, altered size distribution) and the amount of HDL cholesterol.…”
Section: Figurementioning
confidence: 99%
“…After a 4-h fast, blood was obtained from the retro-orbital plexus of mice anesthetized with methoxyflurane (PitmanMoore, Mundelein, IL), placed into precooled tubes containing EDTA (final concentration 4 mM), and centrifuged at 2500 ϫ g for 20 min at 4°C, and aliquots of plasma were stored at Ϫ70°C. Total cholesterol (TC), triglycerides (TG), phospholipids (PL), and free cholesterol (FC) were assayed as previously described (32). HDL-cholesterol was determined as the cholesterol remaining in the plasma after precipitation of apoB-containing lipoproteins with dextran sulfate (Ciba-Corning, Oberlin, OH).…”
Section: Quantification Of Plasma Lipids Lipoproteins and Apolipoprmentioning
confidence: 99%